Feasibility and content validity of the PERF-FIT test battery to assess movement skills, agility and power among children in low-resource settings - Bouwien C. M. Smits-Engelsman; Emmanuel Bonney; Jorge Lopes Cavalcante Neto; Dorothee L. Jelsma (BMC, 2020)
Abstract Background Numerous movement skills and physical fitness tests have been developed for children in high-income countries. However, adaptation of these tests to low-resource settings has been slow and norms are still unavailable for children living in low-income communities. The aim of this paper was to describe the development and validation of the Performance and Fitness (PERF-FIT) test battery, a new test to assess motor skill-related physical fitness in children in low-resource settings. Method The PERF-FIT test was developed in a stepwise manner. This involved defining the relevant domains of the construct of interest and selecting and evaluating test items. The Content Validity Index (CVI) was used to estimate content validity. Following development of the PERF-FIT test, a preliminary study was performed to validate items and to examine the feasibility of implementing the test in a low-resource community. Structural validity was also determined based on data from eighty (n = 80) children (aged 7-12 years) using principal component analysis. Results The CVI for the throw and catch item was 0.86 and 1.00 for the other nine items, leading to a total CVI score of 0.99. The hierarchical sequence of the item series was demonstrated by highly significant (p < 0.001) linear trends, confirming the increase in difficulty of subsequent items. Principal component analysis revealed three factors; the first component is represented by locomotor skills that require static and dynamic balance, the second component by throwing and catching items and the third component by agility and power items. These findings suggest that it is feasible to implement the PERF-FIT in low-resource settings. Conclusion The PERF-FIT test battery is easy to administer and may be suitable for measuring skill-related physical fitness in in low-resource settings. It has excellent content validity and good structural validity. After minor adaptions, further studies should be conducted to establish normative values, evaluate reliability, and document criterion and cross-cultural validity of this test.